INTERVIEW WITH SIMONE BENCK:: CREATION OF THE UNIVERSITY OF THE FEDERAL DISTRICT (UNDF) - Quiroga, Fernando Lionel (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2022)
The trajectory of the creation of the Universidade do Distrito Federal (UnDF) began in the 1990s and materialized, after more than three decades and countless attempts, through the publication of Complementary Law n.º 987 (Distrito Federal, 2021a) authorizes its creation. More than a legal expression, the framework is representative of the efforts of higher education expansion policies that aim to meet the historical demands for the reduction of social inequalities and qualification for the world of work. The project to create the University of the Federal District has been widely discussed with several groups, such as the political, academic-scientific, students, representatives of social movements and civil society itself. In this historical process, highligting the main ideas that have been shaping the creation of yet another Brazilian university.
Keywords: University of the Federal District (Undf). Creation. University education. Challenges.